PENGARUH MODEL PEMBELAJARAN EXPERIENTIAL DENGAN BANTUAN MEDIA PEMBELAJARAN POWERPOINT TERHADAP HASIL BELAJAR SISWA DI SMA NEGERI 2 TENGGARONG SEBERANG - Meliana, Meliana; Sudarman, Sudarman; Rahayu, Vitria Puri (Faculty of Teacher Training and Education, Mulawarman University, 2023)
This research aims to determine whether or not there is an influence from the use of the experiential learning model with the help of PowerPoint learning media on student learning outcomes in economics subjects for class X SMA Negeri 2 Tenggarong Seberang. The method used in this research is a quasi-experimental design with a nonequivalent control group design. The research subjects were students in class X 6 as the control class and X 7 as the experimental class with a total of 66 students. The data collection technique used is a written test in the form of multiple choice and documentation. Analysis of learning outcomes using the t-test which showed a value of 0.008 < 0.05. This means that there is a significant difference between student learning outcomes in the experimental class and the control class, so it can be concluded that there is an influence of the use of the experiential learning model with the help of PowerPoint learning media on student learning outcomes in economics subjects for class X SMA Negeri 2 Tenggarong Seberang.